The influence of cavity design for cusp coverage on fracture strength of weakened maxillary first premolars using two esthetic restorative systems (CAD/CAM hybrid ceramic and nanohybrid composite) (An in vitro study) - Zainab S Jawad; Abdul Karim J Al-Azzawi (College of Dentistry/ University of Baghdad, 2015)
Background: Maxillary first premolar with wide MOD cavity more susceptible to fracture. The aim of this study was to assess the influence of cavity design for cusp coverage on the fracture resistance of weakened maxillary first premolar restored with CAD/CAM hybrid ceramic versus nanohybide composite. Materials and Methods: Fifty six intact maxillary first premolars of approximately comparable sizes were divided into seven groups eight for each: Group A: Intact teeth (control group); Group B: teeth prepared for MOD inlay; Group C: teeth prepared for MOD onlay covering the lingual cusp; Group D: teeth prepared for MOD covering buccal and lingual cusps ,the previous three groups indirectly restored with nanohybrid composite (3M ESPE Z 250 XT); Group E,F,G prepared with the same design as group B, C, D respectively and restored with CAD/CAM hybrid ceramic (VITA ENAMIC). Results: An axial compression test was used to measure the fracture strength of experimented teeth. The readings were analyzed statistically by t-test, one way ANOVA and LSD, then the mode of fracture had been examined. The results showed that sound teeth in group (A) had more fracture resistance values than all experimental groups and the difference were highly significant with group (B, E, F, G).When the influence of cavity design tested among composite groups it showed highly significant difference between group (B) and (C)and the highest fracture resistance value was for group(C), whereas the influence of cavity design among Enamic groups showed highly significant difference between group (E) and (G) the highest fracture resistance value was for group(E).T-test between similar designs showed non-significant difference between MOD groups and highly difference between other groups. Conclusions: Cusp coverage increased the fracture resistance of composite groups but result in non-restorable fracture, while Enamic total onlay presented promising fracture resistance with favorable mode of fracture. Key words: Fracture resistance, CAD/CAM, hybrid ceramic, VITA ENAMIC, nanohybrid composite, cusp coverage.